PERUBAHAN BUDAYA LOKAL DAN ISLAM BANJAR DALAM AKTIVITAS PENDULANGAN BATU PERMATA KHAS KALIMANTAN SELATAN - Rabiatul Adawiah; Inawati Mohammad Jainie; Halimatus Sakdiah (Pascasarjana UIN ANTASARI Banjarmasin, 2023)
South Kalimantan is not only rich in natural resources, but also rich in culture and religious values. This study aims to describe the local cultural traditions and Islam associated with the activity of